Efektifitas Arang Tempurung Kelapa dalam Menurunkan Kadar Logam Perak dan Kromium pada Limbah Laboratorium - Darma Putra Deni (FT-USNI, 2019)
Laboratorium waste is one of the causes that can contaminate the environment. Heavy metal that can contaminate the environment such as silver metal (Ag) and Cromium metal should be removed.The purposefor this research is for remove silver metal (Ag) and Crom metal from the laboratorium waste.Method thatuse in this reasearch is completely randomized factorial.The result of this analysis is show that charcoalcoconut shell is very effective to reduce silver metal (Ag) 85,49 %; 89,27 %; 93,01 %; 96;71 % and Crommetal (Cr) 13,81 %; 24,73 %; 31,92 %; 38,60 % at the addition of Charcoal coconut shell 0,5 g;1,5 g; 2,5g; 3,5 g in laboratorium waste.Result of varian analysis show thatconfidence level F count > F table atthe 95 % and 99 % , it means that addition of charcoal coconut shell give the significant result for removalof silver metal and Crom meta